Anthropometric characteristics of young venezuelan swimmers by biological maturity status - Guillermo Ramírez; Maritza Landaeta-Jiménez; Maura Vásquez; Betty M. Pérez; Coromoto Macías-Tomei (Universidade Federal de Santa Catarina, 2006)
There is limited information available on the maturation of child and adolescent athletes, considering that maturation is a factor that can affect performance. This study evaluates the anthropometry of 115 male Venezuelan swimmers (aged 7-17), at differing stages of biological maturity. The procedures employed adhere to International Society for the Advancement of Kinanthropometry guidelines. Tanner's stages of genital maturation (G1-5) were used to subdivide the sample into the three categories posited by Nicoletti, prepuberty (G1), initial puberty (G2-3) and advanced puberty (G4-5). Forward stepwise discriminant analysis was performed, using increase in hit rate as the selection criterion. A total of 35 variables were evaluated, from which stretch stature, triceps skinfold, subscapular skinfold, calf girth, relaxed arm girth, body mass, forearm length and thigh length were selected. This set produced a high aggregate hit rate (87%) of original grouped cases. Two linear discriminant functions (LDF1 and LDF2) emerged: LDF1 is capable of discriminating between prepuberty and advanced puberty and consists of stretch stature, body mass, forearm length, thigh length, relaxed arm circumference and calf circumference. LDF2 differentiates initial puberty from the other groups. This second set of discriminant variables comprises triceps skinfold and calf circumference. Confidence intervals demonstrate that two variables for body size, two for subcutaneous fatness, two for skeletal robustness and two for relative muscularity suffice to guide coaches when placing young swimmers into categories that best approximate the variability of maturation. Only triceps and subscapular skinfolds exhibited overlapping intervals in the three categories. RESUMO Existe limitada informação sobre a maturação de crianças e adolescentes atletas, uma vez que a maturação é um fator interveniente na performance. O presente estudo mensurou variáveis antropométricas de 115 nadadores Venezuelanos (idade 7-17 anos), em diferentes estágios de maturação biológica. Os procedimentos antropométricos usados foram os recomendados pela ISAK. Os estágios de maturação genital de Tanner (G-5) foram utilizados para subdividir a amostra nas três categorias sugeridas por Nicoletti: pré-puberal (G1), puberal inicial (G2-3) e puberal avançada (G4-5). Foi utilizada a análise discriminante passo a passa (stepwise), tendo como critério de seleção o aumento da porcentagem de indivíduos classificados corretamente. Foram utilizadas 35 variáveis, das quais foram selecionadas: estatura, dobras cutâneas tríceps e subescapular, perímetros da perna e do braço relaxado, massa corporal, e os comprimentos do antebraço e coxa. Essa análise gerou um novo grupo composto por 87% do grupo original. Duas funções lineares discriminantes (LDF1 e LDF2) emergiram: LDF1 diferenciou os indivíduos pré-púberes dos púberes avançados, tendo incluído as variáveis: estatura, massa corporal, comprimento do antebraço e coxa, e os perímetros do braço e da perna. A segunda função, a LDF2, diferenciou os indivíduos no início da puberdade dos demais grupos. O segundo grupo de variáveis incluiu: a dobra cutânea do tríceps e o perímetro da perna. Os intervalos de confiança demonstraram que duas variáveis de tamanho, duas de gordura subcutânea, duas de robustez esquelética e duas de muscularidade relativa são suficientes para guiar os técnicos, na classificação de jovens nadadores, em categorias que melhor aproximem do seu estágio maturacional. Somente as dobras cutâneas do tríceps e subescapular mostraram superposição dos intervalos de confiança nas três categorias.